PRESERVATION OF INDIAN OIL SARDINE (SARDINELLA LONGICEPS) IN ICE AND CHILLED SEA WATER . PART II- CHANGES DURING STORAGE WITH PARTICULAR REFERENCE TO SALT PENETRATION AND LIPID DETERIORATION DURING C S W HOLDING - KRISHNAKUMAR, S; HIREMATH, G G; MENON, N R (Fishery Technology, 2017)
Oil sardines in prime condition were chilled onboard. Two lots were chilled in CSW (samples C & CI), one lot ice (sample I) and a fourth lot was left un-iced on deck (sample AI). Sample AI was iced after landing and sample CI was taken out of the chilled seawater and. iced. All the four samples were kept in a chilled room for storage studies. Sample C, chilled and stored in CSW, recorded a gradual gain in weight and an increase in salt content of the muscle. Presence of salt did not seem to cause any excessive protein denaturation. Salt extractability decreased at a gradual rate in all cases. Presence of salt seemed to wield no noticeable influence on lipid hydrolysis and subsequent peroxidation. Results of chemical and sensory evaluations highlight this. Holding sardines in CSW gave a product of excellent quality for the first four to five days of storage. Beyond the fifth day of storage quality deteriorated rapidly and there was no noticeable superiority for this sample (sample C) over the onboard iced fish. This was evident in the sensory evaluation as well. However, a storage life of five days in a readily acceptable state is sufficient for the fish to be disposed in the market at a premium sale price over other landings of the same species.